Dance Black America - Hegedus, Chris; Pennebaker, D.A.; Contemporary Arts Media; Pennebaker Associates ([New York : Pennebaker Hegedus Films] : Contemporary Arts Media [distributor], 1990)
Celebrating the evolution of black dance, the film documents a four-day festival of dancers and dance companies held at the Brooklyn Academy of Music in 1983
Title from title screen
A festival by State University of New York and Brooklyn Academy of Music
Narrator, Geoffrey Holder
DVD format
Keywords: African American dance; Dance festivals -- New York (State) -- New York